Effect of Organic Liquid Fertilizertambsil On The Growth and Resultskale Crop Land (Ipomoea Reptans Poir) - Bambang Wicaksono Hariyadi; Mahrus Ali; Yeni Ika Pratiwi (Agricultural Science, 2018)
Liquid organic fertilizer Tambsil is a complete liquid organic fertilizer, which is formulated to meet the needs and challenges of the farmers or entrepreneurs in agriculture and plantations in order to get results or harvest prime. Where the liquid organic fertilizer contains a complete nutrient, both elements of macro and micro elements essential for soil fertility and plant growth. A liquid that can be absorbed by plants through leaf stomata or mouth. Functioning as a stimulator and is very safe for human and animal health as well as a very friendly environment (Anonymous, 2017). The purpose of this study to determine the extent of the effect of the use of urea fertilizer on the growth and yield of Green Spinach (Amaranthus tricolorL.).Research conducted at the Faculty of Agriculture Experimental Station Freedom Surabaya, on the road Ketintang Madya VII-2 Surabaya. This study uses a randomized block design (RAK) consists of six (6) treatment without liquid organic fertilizer (control) and liquid organic fertilizer dose 2,5cc; 5,0cc; 7,5cc; 10,0cc; 12,5cc per liter of water with three (3) replicates and two (2) samples of plants. The results of the study are as follows: a. There is a very real effect on the observation variables plant height, leaf number and fresh weight per plant and plant fresh weight per polybag. b. The treatment dosing liquid organic fertilizer Tambsil 12.5 cc per liter of water to produce growth and yields the highest (maximum dose) kale crop land, although it was not statistically significantly different from the dosage of liquid organic fertilizer Tambsil 10.0 cc per liter of water (Dose The optimum or effective dose).